ASEAN Meta-Analytic Reviews on Health and Exercise Researches: Life Sciences-Health - Dr. Soumendra Saha, Guest Editor (International Journal of Life Science and Pharma Research, 2018)
This special issue was conceived to provide a platform to disseminate outcomes of researches conducted in ASEAN Universities, employing cutting-edge technologies to investigate on intricate and yet unexplored aspects associated with enhancement in sport performance excellence, and factors associated with management of health risk factors as well. Meta-analytic systematic review studies were included, which examined impacts of exercise and behavioural interventions in reducing the level of HbA1c among Malaysian Type 2 Diabetes Mellitus patients. Apart from that, effects of conventional physiotherapy exercise training regimes in enhancing muscle strength and in reduction of pain among female osteoarthritis patients were also investigated.